Koordynacja procesów logistycznych w recyklingu - Krawczyk, Stanisław; Michniewska, Katarzyna (Logistic Processes Co-Ordination in Recycling, 2005)
Polish accession to EU has caused many important changes in domestic and social life of Poland. One of the law changes was establishment of national recycling scheme. The aim was to attain appropriate recycling targets for packaging waste, described in details in the above mentioned law. Recycling in Poland is at the very beginning of its development process and its proper accomplishment depends on clear descriptions of co-ordination rules and wide education of responsible for recycling processes human resources. The research and analysis show that activities according to the rules will allow the companies and economy itself achieve real benefits.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 328-336